Compact monopole antenna for wireless USB dongle applications - Mohamed, Ehab Ali (2013)
In this project, two designs of printed monopole antenna with multiband operation are presented to cover six bands GSM900 (880-960MHz) and GSM1800/1900/UMTS/LTE2300/2500 (1710-2690 MHz). Both of designs are compact and easy to embed in USB dongle with a length less than a quarter wavelength. Both of antennas were designed with good omnidirectional radiation pattern in the azimuth plane with compact radiator size equal to 20 × 18 mm2. The design and simulation process is carried out using CST Studio Suite 2012 software. The proposed antennas are fabricated on FR4 epoxy glass substrate with dielectric constant of 4.3. Measurement of return loss, input impedance, voltage standing wave ratio (VSWR), and bandwidth of the antenna are presented. The simulated and measured results are compared to ensure the antennas have a good performance.